2004
DOI: 10.1080/1356251042000216642
|View full text |Cite
|
Sign up to set email alerts
|

Know what I mean? Enhancing student understanding of assessment standards and criteria

Abstract: In recent years there has been an increasing emphasis in higher education on the explicit articulation of assessment standards and requirements-whether this emanates from calls for public accountability or based on ideas of good educational practice (Ecclestone, 2001). We argue in this paper that a single-minded focus on explicit articulation, whilst currently the dominant logic of higher education, will inevitably fall short of providing students and staff with meaningful knowledge of standards and criteria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
152
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 224 publications
(159 citation statements)
references
References 25 publications
2
152
0
2
Order By: Relevance
“…Coll (2000) argues that there is often a disconnection between course aims and objectives articulated (or as presented in course outlines) by university teaching staff and the assessment regimes associated with the courses. Because of this, O'Donovan, Price & Rust (2004) argue that it is crucial that students understand not only the course educational aims, but the assessment regimes (and whether they seek to facilitate meaningful learning). If the course objectives do actually require linking of concepts, then our work here suggests this may be enhanced by the use of concept mapping.…”
Section: Discussion and Implications For Teachingmentioning
confidence: 99%
“…Coll (2000) argues that there is often a disconnection between course aims and objectives articulated (or as presented in course outlines) by university teaching staff and the assessment regimes associated with the courses. Because of this, O'Donovan, Price & Rust (2004) argue that it is crucial that students understand not only the course educational aims, but the assessment regimes (and whether they seek to facilitate meaningful learning). If the course objectives do actually require linking of concepts, then our work here suggests this may be enhanced by the use of concept mapping.…”
Section: Discussion and Implications For Teachingmentioning
confidence: 99%
“…Orr (2004) argued that the lack of academic cultural capital that students ofen have means that more work on tacit knowledge is also needed. This is reinforced by the research on developing a methodology for transferring both explicit and tacit knowledge with regards to assessment criteria (Rust et al, 2003;O'Donovan et al, 2004;Rust et al, 2005;O'Donovan et al, 2006 andPrice et al, 2007). This in turn has led to more emphasis being placed on the need to create explicit and direct criteria for students to improve their understanding of requirements (Haggis & Pouget, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Orr (2007) observed that Transparency seems to have become confused with the idea of wri8ng things down (Orr 2007: 646). A longitudinal study of assessment prac(ce iden(fied the tacit nature of assessment criteria as a key issue and emphasised the difficulty of transferring tacit knowledge to others (O'Donovan et al, 2001;Rust et al, 2003;O'Donovan et al, 2004). Assessment criteria ofen contain words such as 'analy(cal' and 'cri(cally evaluate', but these words are meaningless without a framework and a common understanding.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However such explicit standards promise more than they can deliver (Hawe 2002) and O'Donovan et al (2004) stress the futility of trying to define standards precisely thereby confirming problems identified by Sadler (1987). He argues that (205) fuzzy standards cannot be transformed into sharp standards by simply using more detailed language.…”
Section: Assumptionmentioning
confidence: 99%